195k views
0 votes
Giovanni justifies whether the expression –4x – 8 is equivalent to Negative 2 (x + 1) minus 2 (x + 3) by letting x = 3 in both expressions. What is the value of each expression when x = 3?

User Abesto
by
5.3k points

2 Answers

3 votes

Answer:

They are equivalent

Explanation:

-4(3)= -12 -8 = -20

-2 (3+1)= -6-2 = -8

-2(3+3)= -6-6 = -12 -8+-12=-20

both equal -20.

User Henryeverett
by
5.1k points
1 vote

Answer:

-20 -20

Explanation:

User Wouter Overmeire
by
4.7k points